COMPUTER EXPERIMENTS WITH FINITE ELEMENTS OF HIGHER ORDER - Khomchenko, А. Н.; Koval, Н. В.; Osipova, Н. В. (Journal of Information Technologies in Education (ITE), 2017)
The paper deals with the problem of constructing the basic functions of a quadrilateral finite element of the fifth order by the means of the computer algebra system Maple. The Lagrangian approximation of such a finite element contains 36 nodes: 20 nodes perimeter and 16 internal nodes. Alternative models with reduced number of internal nodes are considered. Graphs of basic functions and cognitive portraits of lines of zero level are presented. The work is aimed at studying the possibilities of using modern information technologies in the teaching of individual mathematical disciplines.